Analisis Pelaporan SPT Tahunan PPh Pasal 21 Sebelum Dan Sesudah Penerapan Sistem E-Filing Bagi PNS Dinsosnakertrans Kabupaten Nias - Maria Magdalena Bate'e (Jurnal Akuntansi dan Pajak, 2018)
E-Filing system is a system reporting of Annual Tax with online system and real time provided by Directorate General of Taxes. The advantage of e-Filing is that it can reduce the time and expense as well as reporting of annual tax is correct and timely. This research is aimed to know the difference of reporting Annual Income Tax clause 21 before and after the application e-Filing System for civil servants of Social Service, Labor, and Transmigration Nias District. The type of research used is descriptive research with qualitative approach, and the data analysis technic used is reduction data, display data, conclusion and verification, and final conclusion. The study population and sample was all civil servants of Social Service, Labor, and Transmigration Nias District which amounts 25 people. From the result of this research, it is found that all civil servants of Social Service, Labor, and Transmigration Nias District have reported their Annual tax by using e-Filing. The using e-Filing system, the service becomes faster, accurate, timely and can be done anywhere and of course this condition is very different when done manual system. The difference is on description of form notification, procedures of tax calculation, time effectiveness, efficiency, archiving, data delivery, and taxpayer compliance.